The Impact of Digital Media Technology on the press Content Industry – A Field Study on Communicator – - Simbawa, Mayaser Waleed (Journal of Humanities & Social Sciences, 2022)
This study aimed to identify the impact of digital media technologies on creating news materials from the perspective of communicators of Saudi Journalists and Content Creators who’s working in the field of media. The researcher used the Descriptive Approach and relied on the Questionnaire as a data collection tool over a Sample of (150) Saudi Journalists and Content Creators selected from the staff working for Saudi newspapers across the Kingdom of Saudi Arabia. The main results are summarized as follows: There was a positive relationship between journalists' use of digital media technologies in the content creation and the rate of dependence on it, in addition to the presence of statistically significant differences in favor of females in their permanent use. The study also indicated that 74% of communicators use digital media technologies to a large extent in producing content materials, but only 58% showed their familiarity with the methods of its production, as 90.7% of them stressed the need for an independent media production team, which indicates the gap in skills that they should acquire. The communicators agreed that the multiplicity of storytelling is one of the most important effects of the use of digital media technologies in editorial content, while the most prominent difficulties were represented in the time element being an obstacle to learning new technologies, which leads to an increase in their working hours.The study suggests starting a professional training program for Journalists to help them learn new digital media skills to use it in making news stories, push them to acquire Multi-Skilled Journalist potentials.
Keywords: Journalism; digital media; content industry; communication technology; social networking sites